6.4k views
1 vote
Solve.
3(x-4) = -3
How do i slove this

User Tennyson H
by
5.1k points

2 Answers

4 votes

Answer:

You need to do the Distributive Property. This means multiplying the number outside the parenthesis to each number inside.

Explanation:

3(x)=3x

3(-4)=-12

3x+-12=-3

then evaluate using inverse operations to get x=3

User Sdorra
by
5.6k points
4 votes

Answer:


3(x - 4) = - 3 \\ 3x + 12 = - 3 \\ 3x = - 15 \\ x = - 5

Firstly, multiply the number and variable in the perenthesis. Then move the variable on it's own side of the equation. The simplify.

User T McKeown
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.